Reversión tras la Inmunoesterilización en Ovino, Cuy y Conejo. - Bautista Tasigchana, Dayana Paulina (2017)
The domestication of the guinea pig, rabbit, sheep and has allowed a reproduction of on annual rate to a non-seasonal type. However, there are still reproductive parameters to evaluate the effect of exogenous drugs what indicate. The study of this experiment was to evaluate the reversion after the Immunocastration in sheep, guinea pigs and rabbits, in relation to the dynamics of the reproductive system, testicular morphometry and its incidence in the gonadal histology. It was selected 4 guinea pigs, 4 rabbits and 4 male sheep in ages of puberty, respectively, that were located in three experimental groups. Each one of the groups blood samples were obtained before each application of the biological anti-GnRH for hormonal analysis of LH, FSH, and testosterone; in addition to the measurement of testicular morphometry and histology. It was applied to each group a dose of 0.5 ml (1 ml to guinea pigs, rabbits and 2 ml of sheep) biological respectively subcutaneously, with an interval of 15 days. It was analyzed LH, FSH, and testosterone before, during and after the application of the biological in the group of treatments; in addition, gonadal tissue samples were collected for histopathological analysis. For the interpretation of the results of the experiment it was used the t-test statistical analysis to detect the existence of differences among the means of a particular quantitative variable in two groups of data. In the present investigation the application of similar or GnRH antagonists showed their modulating effect -immunosuppressant and reversion of the hypothalamic-pituitary-gonadal to influence the concentration levels of sex hormones LH, FSH, and testosterone in guinea pigs, rabbits and sheep. Therefore, the vaccine of Immunocastration proves to be efficient with respect to the estimated effect of suppression of testicular function; however the effects of the reversal presented with greater dynamism in guinea pigs and rabbits to sheep. In addition, in relation to the dynamics of concentration of sex hormones these presented reversal, that is maintained or increased the concentration levels of FSH, LH and testosterone after 60 days of application and withdrawal of the vaccine. In conclusion, it is determined that there are differences by species with respect to the reversal and this could be progressive.